Students's perspectives on pharmacy curriculum in a Malaysian university - Al-Efan, Qais Muhammad Ahmad; Nik Mohamed, Mohamad Haniki; Awaisu, Ahmed; Abdul Razak, Tariq; Ab Rahman, Jamalludin (Penerbit USM, 2009)
Institutions of higher learning are working hard to provide effective, high quality educational programs. Meanwhile, potential students are also looking at “quality” as a metric to help make their decisions about which college to join. Mechanisms to evaluate the quality of higher education offered in universities are already available. This study aimed to determine students’ attitudes and opinions regarding the pharmacy curriculum at the International Islamic University Malaysia (IIUM). A survey instrument was administered to all final year bachelor of pharmacy (BPharm) students. Forty students (93%) completed and returned the survey. The majority of students (75%) expressed their satisfaction regarding the curriculum in general. Most students (74%) were also satisfied with the courses offered by the department of pharmacy practice. However, students were not satisfied with certain issues such as overlapping of some pharmacy practice courses, and the inclusion of the Malaysian language course in the BPharm curriculum.